THE DEVELOPMENT OF MACROMEDIA FLASH 8 BASED ON LEARNING MEDIA ON ARITHMETIC SOCIAL SUBJECT FOR GRADE VII - Intan Permatasari Oktiviani; Uus Kusdinar (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
Learning media in the learning process of mathematics can help students understand the abstract mathematical concept and make learning more exciting and interactive. However, in reality, at school, the availability of instructional media is still limited. This study aims to develop a suitable learning media based on Macromedia flash eight on the arithmetic social subject for grade VII SMP/MTs in learning mathematics. The research includes research and development using Research and Development (R&D) research methods with the following steps: potential and problem, data collection, product design, design validation, design improvement, product testing, product revision, trial use, product revision, and the final product. The research subjects are media experts, subject experts, and students of grade VII State Junior High School 1 Yogyakarta (SMP N 1 Yogyakarta) and State Junior High School 1 Kalasan (SMP N 1 Kalasan). The data are analyzing techniques using qualitative analysis that converted into a form of quantitative value. The data collecting techniques are using interviews, observations, and questionnaires. The product of learning media that has been developed was assessed and validated by three math experts learning media and three math experts learning subject. The assessment of media experts resulted in an outstanding qualitative category. The assessment of subject experts resulted in an outstanding qualitative category, and the student assessment resulted in an excellent qualitative category. Based on those results, it can be concluded that the learning media that has been developed is appropriate for the use of the mathematics learning process.